"FROM REALISM TO MODERNISM" (Conference Zone, 2022)
The art of modernism manifests itself in different ways in different areas. delicate, he was like in the early stages of the avant-garde. Modern artists, especially in appearance, have brought original freedom to the authors, created a new set of operations, and even created original works that reflected the shock of the audience. In Russian literature, this trend has replaced the classic novel. The main directions were futurism, acmeism, symbolism. They have their own characteristics and differ from each other. All this can be seen in the reading of poetry in the first half of the twentieth century. Thus, the second goal separates modernism from realism.